Impact of vehicle fleet characteristics on ambient PM concentrations during rainy season at Farm Gate (CAMS-2) in Dhaka - Begum, BA; Hossain, A; Saroar, G; Nahar, N; Nasiruddin, M (Bangladesh Journal of Scientific and Industrial Research, 2013)
The impact of vehicle fleet characteristics on ambient particulate matters (both PM2.5 and PM10) concentrations during the rainy season was investigation. Sampling was carried out at the continuous air monitoring station (CAMS-2) at the Farm Gate site, a location near a major traffic intersection. It was observed from the analysis, that the PM2.5 concentrations were not varying so much between day and night time. This might be due to the rainfall and high humidity during these days. As the PM2.5 is less, so BC/PM2.5 becomes high compared to winter season. Therefore PM2.5 /PM10 ratio is also less compared to winter time, as PM2.5 is the part of PM10. The black carbon (BC) value is less during this period compared to winter due to both local and meteorological effect. It was also found that although there was heavy rainfall on 13 July 2010, the PM concentration is also high. It may be due to the contribution of sea salt to PM. Bangladesh J. Sci. Ind. Res. 48(2), 143-150, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15746